The current status of pistachio pests in Iran - Mehrnejad M.R. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
In this study, the injurious pests of pistachio orchards in Iran are considered, they were classified into three groups based on economic damage and distribution.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)